2012
DOI: 10.18632/oncotarget.546
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-targeted therapy of human experimental urinary bladder cancers with cytotoxic LH-RH analog AN-152 (AEZS-108)

Abstract: Many bladder cancers progress to invasion with poor prognosis; new therapeutic methods are needed. We developed a cytotoxic LH-RH analog, AN-152 (AEZS-108) containing doxorubicin (DOX), for targeted therapy of cancers expressing LHRH receptors. We investigated the expression of LH-RH receptors in clinical bladder cancers and in HT-1376, J82, RT-4 and HT-1197 human bladder cancer lines. The effect of analog, AN-152, on growth of these tumor lines xenografted into nude mice was analyzed. Using molecular and func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
45
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(46 citation statements)
references
References 52 publications
1
45
0
Order By: Relevance
“…About 70%-80% of human ovarian cancers and about 80% of human endometrial carcinomas express LHRH receptors. The receptors are expressed in 86% of prostate cancers [28] and in all bladder cancers examined [29] as well as 46%-69% of uveal melanomas [30]. These findings all suggest a clinical utility for the presence of the receptor.…”
Section: Discussionmentioning
confidence: 77%
“…About 70%-80% of human ovarian cancers and about 80% of human endometrial carcinomas express LHRH receptors. The receptors are expressed in 86% of prostate cancers [28] and in all bladder cancers examined [29] as well as 46%-69% of uveal melanomas [30]. These findings all suggest a clinical utility for the presence of the receptor.…”
Section: Discussionmentioning
confidence: 77%
“…In particular, GHRH can induce the differentiation of ovarian granulosa cells and other cells in the reproductive system and function as a growth factor in various normal tissues, benign tumors, and malignancies (2-4, 6, 11, 14-18). Previously, we also reported that antagonistic cytototoxic derivatives of some of these neuropeptides are able to inhibit the growth of several malignant cell lines (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14).…”
mentioning
confidence: 89%
“…The dismal outcome of this malignancy demands great efforts to find improved methods of treatment (1). Many compounds have been synthesized in our laboratory in the past few years that have proven to be effective against diverse malignant tumors (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14). These are peptide analogs of hypothalamic hormones: luteinizing hormone-releasing hormone (LHRH), growth hormone-releasing hormone (GHRH), somatostatin, and analogs of other neuropeptides such as bombesin and gastrin-releasing peptide.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11][12][13][14][15][16][17][18][19] Growth hormone-releasing hormone (GHRH), released by the hypothalamus, regulates the secretion of growth hormone (GH) by an action on specific receptors (GHRH-R) for GHRH in the pituitary gland. [7][8][9] In turn, GH induces the production of hepatic cancer specimens and multiple cancer cell lines.…”
Section: Introductionmentioning
confidence: 99%